Islamic Boarding Schools and Transmission of Islamic Values: Internalization of Moderation and Tolerance At Al Hikmah Tuban Islamic Boarding School - Abidin, Zainal (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
This research used a qualitative approach because all facts, both oral and written, from the data source were observed, and field notes and other related documents were described by the original and then reviewed to find the findings obtained. This research produced descriptive data. Qualitative research using descriptive methods was a problem-solving procedure investigated by describing the state of the research object based on visible facts or as they were. The descriptive method focused on finding facts as the actual situation. Using descriptive qualitative research, it was hoped that the data obtained would be more complete, profound, and meaningful to achieve the research objectives. The research results showed that the basic concept of kashruth and tasamuh attitudes in Pondok Pesantren Al-Hikmah Tuban has been implemented in everyday life as evidenced by some activities, including: a). The placement of wakam (room) does not differentiate the students' origin, race, ethnicity, region, or descent. b). Bahtsul masai'l is a place for students to accept differences. c). Upholding tolerance, mutual respect, and helping each other. Internalization: The attitudes of tawasuth and tasamuh in Pondok Pesantren Al-Hikmah Tuban were implemented smoothly because the activities of the students were directly monitored by the founder and caretaker (KH.M Husnan Dimyati), assisted by the board of boarding schools, the attitude of tawasuth and tasamuh is always taught in pesantren, and it was proven by the behavior of these students who uphold differences, respect, love and help each other and the activities of the students who showed tawasuth and tasamuh behavior in everyday life.